Participação e controle social em saneamento no contexto da reparação de danos do desastre em Brumadinho - Alisson Martins Ramos (2023)
The disaster that occurred in Brumadinho generated, in addition to the enormous loss of human life and environmental damage, impacts on the water supply. This occurred directly in water sources with suspended abstractions, some for a long period. There were also impacts on infrastructure, which made supply in the territories of municipalities along the Paraopeba River unfeasible. In this context, the impacts and damages resulting from disasters cause great commotion and can encourage mobilization and social participation in the affected areas. This work seeks to analyze perspectives of social participation and social control in basic sanitation with regard to the repair of damages resulting from the collapse of the Córrego do Feijão dam, in Brumadinho, under the responsibility of Vale S. A.. To this end, methodological procedures were carried out from of qualitative research techniques, with the collection of official documents - agreements between the parties, minutes of meetings from social control structures and other bodies linked to the State Policy for People Affected by Dams aimed at repairing sanitation damage. In addition, semi-structured interviews were identified, selected and conducted with social actors directly or indirectly related to the subject and its developments. These interviews covered discussions and actions relevant to three specific themes: Participation and Social Control in Sanitation; Social Networks and Actors in the context of Damage Repair; and Alignment of suggested solutions with the Human Rights to Water and Sanitation. It was noted that social participation in sanitation was encouraged, but was not accompanied by social control, with demands and discussions taking place in different spaces. Despite the tragedy that befell the region affected by the disaster having encouraged the mobilization and social participation of affected groups, results point to low social participation in issues related to sanitation. Thus, the main guiding hypothesis of this research was validated in relation to social participation. However, it was not validated in relation to social control, given that the official sphere of discussion, represented by the councils, did not encourage or facilitate the discussion of topics linked to sanitation and the direct and indirect repercussions of the disaster on them. The study also pointed to the creation of dynamic and fluid networks formed by affected people and social movements. It was found that the conducts that permeated the reparation process, regarding water supply and sewage, are decisive for the failure to realize the Human Rights to Water and Sanitation. The water treatment technologies were proposed by Vale, to meet the demands of residents located close to the Paraopeba River, in rural areas. Criticism focused on the distancing of local cultures and lack of concern for the interests of the communities. In view of the findings of this research, it is recommended that new studies be carried out that explore the vision of traditional peoples. Furthermore, it is recommended to develop sanitation solutions aligned with their way of life. It is also recommended that studies focus on strengthening structures of participation and social control in sanitation, in repairing damage in disasters.